THE EFFECT OF COMMUNICATIVE LANGUAGE TEACHING ON THE STUDENTS’ ACHIEVEMENT IN WRITING HORTATORY - Fatin Nadifa Tarigan; Rahmad - Husein (Universitas Negeri Medan, 2014)
Abstract This study deals with the effect of Communicative Language Teaching on the students’ achievement in writing hortatory. The objective of this study is to find out whether Communicative Language Teaching significantly affects students’ achievement in writing hortatory. This study was conducted by experimental research. The population of this research was grade XI students of MAN Aek Natas. The sample was class XI-IPA with 36 students. The students were divided into experimental and control group. The experimental group was taught using CLT approach and the control group was taught without using CLT approach. The data were analyzed by using t-test formula to find out the t-observed, which was compared to the t-table in level of 0.05. It is found that the t-observed is higher than t-table (t-observed= 3.855 > t-table =2.102 ; p =0.05) meaning that Communicative Language Teaching has significant effect on the students’ achievement in writing hortatory. Key words: Communicative Language Teaching, Writing, Hortatory.